Biosynthetic Plasticity Enables Production of Fluorinated Aurachins. (5th May 2020) - Sester, Angela; Stüer‐Patowsky, Katrin; Hiller, Wolf; Kloss, Florian; Lütz, Stephan; Nett, Markus
Abstract: Enzyme promiscuity has important implications in the field of biocatalysis. In some cases, structural analogues of simple metabolic building blocks can be processed through entire pathways to give natural product derivatives that are not readily accessible by chemical means. In this study, we explored the plasticity of the aurachin biosynthesis pathway with regard to using fluoro‐ and chloroanthranilic acids, which are not abundant in the bacterial producers of these quinolone antibiotics. The incorporation rates of the tested precursor molecules disclosed a regiopreference for halogen substitution as well as steric limitations of enzymatic substrate tolerance. Three previously undescribed fluorinated aurachin derivatives were produced in preparative amounts by fermentation and structurally characterized. Furthermore, their antibacterial activities were evaluated in comparison to their natural congener aurachin D. Abstract : Room for a halogen : The plasticity of the aurachin biosynthetic pathway in the myxobacterium S. erecta was explored for the use of fluoro‐ and chloroanthranilic acids. Incorporation of the unnatural precursors was quantified. Three fluorinated aurachin analogues were produced in sufficient quantity to enable their antibacterial activities to be assessed.